Urolithiasis: from past to present - Nikitin , Oleg; Samchuk , Pavlo; Krasiuk , Oleksii; Korytskyi , Andrii; Nasheda , Serhii (The Ukrainian Scientific Medical Youth Journal, 2023)
Urolithiasis is a polyetiological disease associated with metabolic disorders and characterized by the formation of stones in the urinary tract. Today, it has become a global problem. The incidence and prevalence of urolithiasis have been on the rise, it depends on geographical, climatic, ethnic, dietary and genetic factors. Upper urinary tract stones affect mainly men (approximately 3 times more often than women). The lifetime risk of stone formation is on average 5 to 10%. The prevalence of urinary stones in different regions ranges from 1% to 20%. In countries with a high standard of living, such as Sweden, Canada, or the United States, the prevalence is more than 10%. In some regions, there has been an increase in rates of more than 37% over the past 20 years. In Ukraine, urolithiasis ranks second among all urological diseases, with more than 52 thousand patients registered annually for the first time, and the incidence ranges from 30 to 45% among all urological pathologies. Mostly young people are affected, and the disease is associated with acute and chronic pyelonephritis and frequent recurrence of urinary stones (30-80%). This course of urolithiasis leads to renal failure, disability, and mortality. The stone formation is a complex and polyetiological process that includes endogenous (age, gender, and heredity) and exogenous factors (geographical conditions, climate, and nutrition). It is known that humanity has been suffering from this disease for over 7000 years. Urolithiasis has been well known for centuries. It is clearly confirmed by various archaeological findings, as well as scriptures about painful calculi and therapeutic procedures that were performed to remove them. Given the importance and prevalence of urolithiasis, this article reviews the historical development of the diagnosis and treatment of this disease in different regions of the world. A review of the methods of diagnosis and treatment from early antiquity to the most modern ones that are in use today.